(2c-3d)-(-7c-2d)
This is simply 2c-3d+7c+2d = 9c-d.
The negative sign is distributed.
- (-7c) = + 7c
- (-2d) = +2d
The leftover terms can be combined.
2c +7c = 9c and -3d +2d = -d
Thus, the final answer is:
9c-d
2006-11-22 09:33:52
·
answer #1
·
answered by stringbean 3
·
0⤊
0⤋
DEVELOP THE MATH TERM:
(2c-3d)-(-7c-2d) ==>
First, we solve the parentheses:
Remember that by multiplying the signs always equals to positive.
Otherwise, different signs equals to negative.
Second, we multiply the sign of the element outside by
every inside. First signs and later the numbers. So, we
have:
2c -3d + 7c + 2d ==>
If we group the c's and the d's, we have:
(2 + 7)c + (-3 + 2)d ==>
9c -d
Then, (2c-3d)-(-7c-2d) is:
9c -d
2006-11-22 17:58:02
·
answer #2
·
answered by theWiseTechie 3
·
0⤊
0⤋
(2c-3d) - (-7c-2d)
= 2c - 3d + 7c + 2d
(subtracting a negative number is the same as adding)
= 2c + 7c - 3d + 2d
= 9c - d
2006-11-22 17:35:20
·
answer #3
·
answered by cdndave 2
·
0⤊
0⤋
(2c-3d)-(-7c-2d)
(2c-3d)+(7c-2d) i changed the two negatives to positive
(9c-3d)+(-2d) add 2c and 9c
9c-5d add -3d and -2d
9c-5d is the answer
2006-11-22 17:41:37
·
answer #4
·
answered by happy.girl 5
·
0⤊
0⤋
2c-3d+7c+2d
=c+7c-3d+2d
=8c-d
2006-11-22 17:35:49
·
answer #5
·
answered by raj 7
·
0⤊
0⤋
(2c - 3d) - (-7c - 2d)
2c - 3d + 7c + 2d
9c - d
QED
2006-11-22 18:19:36
·
answer #6
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
(2c-3d)-(-7c-2d)
2c-3d+7c+2d
9c-d
2006-11-22 22:05:15
·
answer #7
·
answered by sam 3
·
0⤊
0⤋
thats easy 9c-d
2006-11-22 17:41:56
·
answer #8
·
answered by SHAMEERSZ TRINI BABIE 2
·
0⤊
0⤋
9c-d
2006-11-22 19:29:12
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
9c-d
2006-11-22 17:41:19
·
answer #10
·
answered by zlisa98 3
·
0⤊
0⤋